Unidirectional spin-wave propagation and devices. (12th November 2021) - Chen, Jilei; Yu, Haiming; Gubbiotti, Gianluca
Abstract: Unidirectional information transport plays a key role in optics, microwave technology, electronic logic circuits and devices. Spin waves (SWs) are considered to be a promising candidate for the next-generation logic devices, which have many advantages such as low-energydissipation and compatibility with radio-frequency-based electronic devices. Unidirectional SWs have been demonstrated in magnetic thin films theoretically and experimentally, offering a great opportunity to realize unidirectional transport of spin information. In this article, we review several methods for emitting and measuring unidirectional SWs, such as using the nonreciprocity provided by magnetostatic surface SWs and interfacial Dzyaloshinskii–Moriya interactions. Unidirectional SWs can also be excited by magnetic nanowire arrays as well as spatially defined spin textures. Finally, we review some magnonic logic devices based on unidirectional SWs, such as spin-wave diodes.